Analysis of basic pentacysteine6 transcription factor involved in abiotic stress response in Arabidopsis thaliana - Zhang, Zhijun; Zhang, Tingting; Ma, Lei (Frontiers in Genetics, 2023)
Abiotic stress is a significant environmental factor that limits plant growth. Plants have complex and diverse mechanisms for dealing with abiotic stress, and different response mechanisms are interconnected. To explore the survival mechanisms of plants under abiotic stress, we used gene expression profile data of Arabidopsis in response to abiotic stress, constructed a weighted gene co-expression network and identified three gene modules that are primarily associated with cold stress, heat stress, and salt stress. Functional enrichment analysis indicated that the genes in these modules participate in biological processes such as protein binding, stress response, and others. Transcription factor enrichment analysis revealed that the transcription factor Basic Pentacysteine6 (BPC6) plays a crucial regulatory role in these three modules. The expression of the BPC6 gene is dramatically affected under a variety of abiotic stress treatments, according to an analysis of Arabidopsis gene expression data under abiotic stress treatments. Differential expression analysis showed that there were 57 differentially expressed genes in bpc4 bpc6 double mutant Arabidopsis relative to normal Arabidopsis samples, including 14 BPC6 target genes. Protein interaction network analysis indicated that the differentially expressed genes had strong interactions with BPC6 target genes within the key modules. Our findings reveal that the BPC6 transcription factor plays a key regulatory function in Arabidopsis coping with a variety of abiotic stresses, which opens up new ideas and perspectives for us to understand the mechanism of plants coping with abiotic stresses.